Analysis Of The Effect Of Service Quality, Marketing Mix, On Interest In Service Reuse Hospitalization - Ahmad Rafli Bintang; Johannes Bastira Ginting; Chrismis Novalinda Ginting (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
The diversity of people's needs for health products and services means that hospitals are competing as much as possible to serve consumers. Hospitals must improve the quality of service and also hospitals need to design marketing programs so that products/services get a response from the target market and run successfully. The marketing mix is a set of marketing tools used by the company to continuously achieve one of the marketing goals, namely to provide satisfaction to the wants and needs of consumers and to generate profits for the company from the mix market. The purpose of this study was to determine the effect of service quality and marketing mix on the intention to reuse inpatient services at RSU Royal Prima Medan in 2022. This research is a type of quantitative research. The research design used was an analytic observational method with a cross sectional approach. The population in this study was the average patient who came for treatment at the Inpatient Installation of RSU Royal Prima Medan in the last 3 months, totaling 1,653 patients. Sampling used SEM analysis where the number of samples was 150 patients. Data analysis used univariate, bivariate and multivariate analysis. The results showed that service quality had a positive and significant effect on the intention to reuse inpatient services at RSU Royal Prima Medan p-value <0.05, the marketing mix had a positive and significant effect on the intention to reuse inpatient services at RSU Royal Prima Medan p-value < 0.05. Simultaneously or simultaneously service quality and marketing mix have a positive and significant effect on the intention to reuse inpatient services at RSU Royal Prima Medan p-value <0.05. The independent variable that has the most influence on the dependent variable in this study is the service quality variable.Keywords: Hospital, Interest in reus, Marketing mix, Quality of service